Holistic Framework as an Approach towards a Relevant and Responsive Community Extension and Development Program: The Case of Sitio Dipanamianan - Olila, Rowel (JPAIR Multidisciplinary Research, 2021)
An integrative, participatory, sustainable, and outcomes-oriented community extension and development activity must have three main elements in the program planning, namely, (1) research, (2) extension activity that focuses on technology dissemination and adoption generated from research findings, and (3) capability building of stakeholders and beneficiaries. Combining all these concepts, the researcher termed these approaches holistic or holistic approaches towards making extension programs relevant and responsive according to the situation and conditions of the community it intends to serve. The research investigated the overall quality of the 5 Year Community Extension and Development Program, the status, and responses of the beneficiaries of the extension program in its adopted community in Sitio Dipanamianan, Brgy. Pingit, Baler, Aurora, Philippines. The researcher used the Community Needs Assessment to describe the beneficiaries’ prevailing conditions and status. The research utilized a mixed-methods research design through the Community Needs Assessment Survey (CNA) and Focus Group Discussion. These were utilized to investigate the participants’ responses, level of participation, and willingness to make the extension activity sustainable and outcomes-oriented. Based on the holistic model, it is found out that the 5 Year Community Extension and Development Program is comprehensive, containing all the principles of the holistic approach. The respondents believed that the holistic approach to extension services is a crucial factor in the sustainability of the program and a high level of participation from the beneficiaries.